O plano de deslocações urbanas e a resposta estratégica que falta aos PROTs e PDMs: A descentralização do planeamento do território e dos transportes - Gaivoto, Carlos F. S. (2009)
The sustainable urban mobility plan is the framework of planning and organisation of mobility system. It is a strategic and operational plan with consequences in the planning and organisation of territorial and transport systems. When it’s defining the principles and the objectives of sustainable development and when it’s working in the scenarios of modal shift more favourable to the alternative modes than the car, the planning and the organisation of territory will be integrated on the political of reduction of road circulation volumes, in the reduction of GEE, waste of space and time, in the improvement of quality of urban environment. The Urbanism Agencies and the Urban Transport Authorities will get their selves in the urban mobility plan, in territory scenarios development, mobility and transports, with the objective to understand the sustainable politics in the accessibilities which are available by the transportation bill. In Portugal, although the authorities are not yet working, the law (1/2009) recently approved in last December and published at the beginning of the year, they have the sustainable urban mobility plans forward in this strategy.